Vanadium dioxide nanowire as well as preparation method and application thereof

Through the optimization of the preparation process, vanadium dioxide nanowires with high specific surface area and excellent conductivity were prepared, which solved the low conductivity and dissolution of vanadium dioxide materials in aqueous zinc ion batteries, and significantly improved the rate performance and cycle stability of the battery.

CN120157175APending Publication Date: 2025-06-17CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510319400.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

In existing aqueous zinc ion batteries, vanadium dioxide materials have low conductivity and dissolution problems during the charge and discharge cycle, resulting in poor rate performance and cycle stability.

Method used

Through the optimization of the preparation process, a mixed reduction reaction of vanadium source, water and reducing agent is used, combined with surfactant and pH adjuster, and hydrothermal reaction is carried out to prepare vanadium dioxide nanowires with high specific surface area, excellent conductivity and mechanical flexibility.

Benefits of technology

It realizes low-cost and high-efficiency vanadium dioxide nanowire production, significantly improving the rate performance and cycle stability of aqueous zinc ion batteries. At a current density of 10A/g, the specific capacity can reach 172mAh/g. After 1000 cycles, the capacity retention rate is as high as 80%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005316998350000011
    Figure HDA0005316998350000011
  • Figure HDA0005316998350000012
    Figure HDA0005316998350000012
  • Figure HDA0005316998350000021
    Figure HDA0005316998350000021
Patent Text Reader

Abstract

The invention provides a vanadium dioxide nanowire as well as a preparation method and application thereof. The preparation method comprises the following steps: a) mixing a vanadium source, water and a reducing agent, and carrying out reduction reaction to obtain a first solution; and b) mixing the first solution obtained in the step a) with a surfactant and a pH regulator, adding a titanium sheet, carrying out a hydrothermal reaction, taking out the reacted titanium sheet, separating a product growing on the titanium sheet, and drying to obtain the vanadium dioxide nanowire. Compared with the prior art, low-cost and high-efficiency production of the vanadium dioxide nanowire is realized by optimizing the preparation process, and the prepared vanadium dioxide nanowire has high specific surface area and excellent conductivity and mechanical flexibility, can effectively improve the rate capability and cycling stability of the aqueous zinc ion battery, and has a wide application prospect. And under the current density of 10A / g, the specific capacity can reach 172mAh / g, and the capacity retention rate reaches up to 80% after 1000 cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous zinc-ion batteries, and more specifically, to a vanadium dioxide nanowire and a preparation method and application thereof. Background Art

[0002] Vanadium dioxide (VO2) is formed by distorted [VO6] octahedrons, and the octahedrons form a tunnel-like skeleton by sharing corners and edges, where the b-axis direction is 0.82 nm 2 , the a-axis direction is 0.34 nm 2 , the c-axis direction is 0.5 nm 2 . This large tunnel structure is beneficial to the rapid intercalation and deintercalation of zinc ions and has good rate performance.

[0003] However, the low conductivity of VO2 materials and the dissolution problem of VO2 during the charge-discharge cycle lead to poor rate performance and cycle stability of aqueous zinc-ion batteries. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide a vanadium dioxide nanowire and a preparation method and application thereof. By optimizing the preparation process, the production of vanadium dioxide nanowires with low cost and high efficiency is realized, and the prepared vanadium dioxide nanowires have a high specific surface area, excellent conductivity and mechanical flexibility, which can effectively improve the rate performance and cycle stability of aqueous zinc-ion batteries.

[0005] The present invention provides a preparation method of vanadium dioxide nanowires, including the following steps:

[0006] a) Mix a vanadium source, water and a reducing agent, and carry out a reduction reaction to obtain a first solution;

[0007] b) After mixing the first solution obtained in step a) with a surfactant and a pH regulator, add a titanium sheet, carry out a hydrothermal reaction, take out the reacted titanium sheet, separate the product grown on the titanium sheet, and dry it to obtain vanadium dioxide nanowires.

[0008] Preferably, in step a), the vanadium source is selected from one or more of vanadium pentoxide, ammonium metavanadate, ammonium polyvanadate;

[0009] The reducing agent is selected from one or more of oxalic acid, citric acid, tartaric acid.

[0010] Preferably, in the process of mixing the vanadium source, water and the reducing agent in step a), the molar concentration of the vanadium source is controlled to be 0.1 mol / L to 0.5 mol / L;

[0011] The molar ratio of the vanadium source to the reducing agent is 1:(2 - 4).

[0012] Preferably, the temperature of the reduction reaction in step a) is 90 °C to 100 °C, and the time is 1 h to 4 h.

[0013] Preferably, the surfactant in step b) is cetyltrimethylammonium bromide, and the mass fraction after addition is 0.5% to 2.0%.

[0014] Preferably, the pH regulator in step b) is ammonia water, and the pH value is adjusted to 4 to 6.

[0015] Preferably, the temperature of the hydrothermal reaction in step b) is 160 °C to 200 °C, and the time is 8 h to 16 h.

[0016] Preferably, the separation process in step b) is specifically as follows:

[0017] After washing the reacted titanium sheet with water, it is placed in water and sonicated for 10 min to 30 min, and after filtration, the product grown on the titanium sheet is separated;

[0018] The drying temperature is 60 °C to 80 °C, and the time is 10 h to 15 h.

[0019] The present invention also provides a vanadium dioxide nanowire prepared by the preparation method described in the above technical solution.

[0020] The present invention also provides a zinc ion battery, including a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes the vanadium dioxide nanowire described in the above technical solution.

[0021] The present invention provides a vanadium dioxide nanowire, its preparation method and application; the preparation method includes the following steps: a) mixing a vanadium source, water and a reducing agent, and performing a reduction reaction to obtain a first solution; b) mixing the first solution obtained in step a) with a surfactant and a pH regulator, adding a titanium sheet, performing a hydrothermal reaction, taking out the reacted titanium sheet, separating the product grown on the titanium sheet, and drying to obtain vanadium dioxide nanowires. Compared with the prior art, the present invention realizes the production of vanadium dioxide nanowires with low cost and high efficiency by optimizing the preparation process, and the prepared vanadium dioxide nanowires have a high specific surface area, excellent conductivity and mechanical flexibility, which can effectively improve the rate performance and cycle stability of aqueous zinc ion batteries. At a current density of 10 A / g, the specific capacity can reach 172 mAh / g, and after 1000 cycles, the capacity retention rate is as high as 80%. Description of the Drawings

[0022] Figure 1 XRD pattern of the VO2 nanowires prepared in Example 1 of the present invention;

[0023] Figure 2Scanning electron microscope image of the VO2 nanowires prepared in Example 1 of the present invention;

[0024] Figure 3 Rate performance curve of the VO2 nanowires prepared in Example 1 of the present invention;

[0025] Figure 4 Cycling performance graph of the VO2 nanowires prepared in Example 1 of the present invention. Detailed implementation manners

[0026] Next, in combination with the embodiments of the present invention, the technical solutions of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0027] The present invention provides a method for preparing vanadium dioxide nanowires, comprising the following steps:

[0028] a) Mix a vanadium source, water, and a reducing agent, and carry out a reduction reaction to obtain a first solution;

[0029] b) After mixing the first solution obtained in step a) with a surfactant and a pH regulator, add a titanium sheet, carry out a hydrothermal reaction, take out the reacted titanium sheet, separate the product grown on the titanium sheet, and dry it to obtain vanadium dioxide nanowires.

[0030] The present invention first mixes a vanadium source, water, and a reducing agent, and carries out a reduction reaction to obtain a first solution.

[0031] In the present invention, the vanadium source is preferably selected from one or more of vanadium pentoxide, ammonium metavanadate, and ammonium polyvanadate, and more preferably vanadium pentoxide. The present invention has no special limitation on the source of the vanadium source, and commercially available products well-known to those skilled in the art can be used.

[0032] In the present invention, the water is preferably deionized water.

[0033] In the present invention, the reducing agent is preferably selected from one or more of oxalic acid, citric acid, and tartaric acid, and more preferably oxalic acid, citric acid, or tartaric acid. The present invention has no special limitation on the source of the reducing agent, and commercially available products well-known to those skilled in the art can be used.

[0034] In the present invention, in the process of mixing the vanadium source, water, and the reducing agent, that is, the process of dissolving the vanadium source and the reducing agent in water, the molar concentration of the vanadium source is preferably controlled to be 0.1 mol / L to 0.5 mol / L, specifically it can be: 0.1 mol / L, 0.2 mol / L, 0.5 mol / L.

[0035] In the present invention, the molar ratio of the vanadium source to the reducing agent is preferably 1:(2 - 4), specifically it can be: 1:2, 1:3, 1:4.

[0036] In the present invention, the temperature of the reduction reaction is preferably 90°C - 100°C, and the time is preferably 1h - 4h; the reduction reaction is preferably carried out under stirring conditions to obtain a solution in which all the solid phase is dissolved, that is, the first solution.

[0037] After obtaining the first solution, in the present invention, the obtained first solution is mixed with a surfactant and a pH regulator, then a titanium sheet is added, and a hydrothermal reaction is carried out. The titanium sheet after the reaction is taken out, the product grown on the titanium sheet is separated, and after drying, vanadium dioxide nanowires are obtained.

[0038] In the present invention, the surfactant is preferably cetyltrimethylammonium bromide (CTAB). After adding it, it is stirred and dissolved, and its mass fraction is preferably controlled to be 0.5% - 2.0%. The purpose of adding CTAB in the present invention is to control the growth direction of the product.

[0039] In the present invention, the pH regulator is preferably ammonia water. After adding it, the pH value is preferably adjusted to 4 - 6.

[0040] The present invention has no special restrictions on the sources of the above-mentioned surfactant and pH regulator, and commercially available products well-known to those skilled in the art can be used.

[0041] In the present invention, after the obtained first solution is mixed with a surfactant and a pH regulator, a second solution is obtained, and then a titanium sheet is further added for hydrothermal reaction.

[0042] In the present invention, before adding the titanium sheet, it is preferably pretreated first; the process of the pretreatment is preferably specifically:

[0043] The pure titanium sheet is successively polished with sandpapers of 400 mesh, 800 mesh and 1200 mesh, and then ultrasonically cleaned in an ethanol solution. The present invention has no special restrictions on the source of the pure titanium sheet, and commercially available products well-known to those skilled in the art can be used. In the present invention, the role of the titanium sheet is to serve as a current collector and a substrate for the growth of vanadium dioxide.

[0044] In the present invention, the hydrothermal reaction is preferably carried out in a hydrothermal reaction kettle well-known to those skilled in the art; the temperature of the hydrothermal reaction is preferably 160°C - 200°C, more preferably 160°C - 180°C, and the time is preferably 8h - 16h, more preferably 8h - 12h.

[0045] Finally, in the present invention, the titanium sheet after the reaction is taken out, the product grown on the titanium sheet is separated, and after drying, vanadium dioxide nanowires are obtained.

[0046] In the present invention, vanadium dioxide grows on the titanium sheet after the reaction; the separation process is preferably specifically as follows:

[0047] After washing the titanium sheet after the reaction with water, it is placed in water and ultrasonically treated for 10 min to 30 min. Vanadium dioxide detaches from the titanium sheet, and after filtration, the product grown on the titanium sheet is separated.

[0048] In the present invention, the drying temperature is preferably 60 °C to 80 °C, and the time is preferably 10 h to 15 h. A vacuum drying oven well-known to those skilled in the art can be used.

[0049] The present invention provides a preparation method of a vanadium dioxide nanowire material. Using vanadium pentoxide, ammonium metavanadate, and ammonium polyvanadate as raw materials, it is reduced to a tetravalent vanadium solution by a reducing agent, then a surfactant is added, and after adjusting the pH of the solution with ammonia water, the solution and the pre-treated titanium sheet are transferred into a hydrothermal reaction kettle for reaction to prepare VO2 nanowires. The high specific surface area, excellent electrical conductivity, and mechanical flexibility brought by its one-dimensional nanostructure can effectively improve the rate performance and cycle stability of aqueous zinc-ion batteries.

[0050] The preparation method provided by the present invention has a simple process route, mild and easy-to-control conditions, low cost, and high efficiency, and has broad application prospects.

[0051] The present invention also provides a vanadium dioxide nanowire, which is prepared by the preparation method described in the above technical solution; as an electrode material, this VO2 nanowire is applied to zinc-ion batteries, which can effectively improve the rate performance and cycle stability of aqueous zinc-ion batteries and significantly improve the electrochemical performance of the material.

[0052] In the present invention, the diameter of the vanadium dioxide nanowire is 30 nm to 150 nm, and the length is 5 μm to 10 μm.

[0053] The present invention also provides a zinc-ion battery, including: a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode includes the vanadium dioxide nanowire described in the above technical solution.

[0054] Vanadium dioxide is considered to be one of the most promising positive electrode materials for aqueous zinc-ion batteries. Due to the low working voltage and poor cycle stability of vanadium-based materials, the commercial application of Zn / VO2 aqueous batteries is limited. The present invention significantly improves the conductivity and cycle stability of VO2 by preparing a VO2 nanofiber electrode material, greatly improving the rate performance and cycle stability of VO2-based aqueous zinc-ion batteries, and having good promotion and application prospects.

[0055] The present invention provides a vanadium dioxide nanowire, a preparation method thereof and an application; the preparation method comprises the following steps: a) mixing a vanadium source, water and a reducing agent, and performing a reduction reaction to obtain a first solution; b) mixing the first solution obtained in step a) with a surfactant and a pH regulator, adding a titanium sheet, performing a hydrothermal reaction, taking out the reacted titanium sheet, separating the product grown on the titanium sheet, and drying to obtain vanadium dioxide nanowires. Compared with the prior art, the present invention realizes the production of vanadium dioxide nanowires with low cost and high efficiency by optimizing the preparation process, and the prepared vanadium dioxide nanowires have a high specific surface area, excellent conductivity and mechanical flexibility, which can effectively improve the rate performance and cycle stability of an aqueous zinc ion battery. At a current density of 10 A / g, the specific capacity can reach 172 mAh / g, and after 1000 cycles, the capacity retention rate is as high as 80%.

[0056] To further illustrate the present invention, the following examples are used for detailed description. All raw materials used in the following examples of the present invention are commercially available, and the titanium sheet is pretreated: the pure titanium sheet is polished successively with 400-mesh, 800-mesh and 1200-mesh sandpapers, and then ultrasonically cleaned in an ethanol solution.

[0057] Example 1

[0058] (1) Disperse vanadium pentoxide powder in deionized water, and control the molar concentration at 0.2 mol / L; then add citric acid as a reducing agent, and the molar ratio of the reducing agent to vanadium pentoxide is 2:1. Then heat to 90 °C and stir for 2 h at the same time to completely dissolve the vanadium pentoxide powder to form a blue solution, denoted as solution A.

[0059] (2) Add CTAB to solution A and stir to dissolve it, control the mass fraction of CTAB at 0.5%, and adjust the pH of the solution to 5 with ammonia water to obtain solution B.

[0060] (3) Transfer solution B and the titanium sheet into a hydrothermal reaction kettle, control the reaction temperature at 160 °C and the reaction time at 8 h; after the reaction is completed, take out the titanium sheet, wash it with deionized water and ultrasonically clean it for 10 min, filter it and place it in a vacuum drying oven at 60 °C for drying for 10 h to obtain vanadium dioxide nanowires.

[0061] The product characterization results are shown in Figures 1-2 as follows, where Figure 1 is the XRD pattern of the VO2 nanowires prepared in Example 1 of the present invention; Figure 2 is the scanning electron microscope image of the VO2 nanowires prepared in Example 1 of the present invention. It can be seen from Figure 2 that the product is nanowires with a diameter of 50-100 nm and a length of 5-10 μm.

[0062] Application Example 1

[0063] The VO2 nanowires prepared in Example 1, acetylene black, and polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 8:1:1 as the positive electrode, a 0.2 mm commercial zinc foil was used as the negative electrode, and 3M Zn(CF3SO3)2 was used as the electrolyte to assemble a battery. After the assembled battery was left standing for 12 h, electrochemical tests were carried out on a Blue Electric test system with a voltage window of 0.2 - 1.6 V.

[0064] The test results are shown in Figures 3-4 as follows, where Figure 3 is the rate performance curve of the VO2 nanowires prepared in Example 1 of the present invention. It can be seen from Figure 3 that at currents of 0.1, 0.2, 0.4, 0.6, 1, 2, 4, 6, and 10 A / g, the specific capacities are 364.5, 349.3, 340.4, 328.2, 316.7, 298.7, 277.4, and 252.6 mAh / g, respectively; Figure 4 is the cycle performance graph of the VO2 nanowires prepared in Example 1 of the present invention. It can be seen from Figure 4 that when this material is used as the positive electrode material of a zinc-ion battery, at a current density of 10 A / g, after 1000 cycles, the capacity reaches 160 mAh / g and the capacity retention rate reaches 72%.

[0065] Example 2

[0066] (1) Vanadium pentoxide powder was dispersed in deionized water with a molar concentration controlled at 0.1 mol / L; subsequently, oxalic acid was added as a reducing agent, and the molar ratio of the reducing agent to vanadium pentoxide was 3:1. Then, it was heated to 90 °C and stirred for 2 h to completely dissolve the vanadium pentoxide powder, forming a blue solution, denoted as Solution A.

[0067] (2) CTAB was added to Solution A and stirred to dissolve, controlling the mass fraction of CTAB to be 1%. The pH of the solution was adjusted to 5 with ammonia water to obtain Solution B.

[0068] (3) Solution B and a titanium sheet were transferred into a hydrothermal reaction kettle, controlling the reaction temperature at 180 °C and the reaction time at 10 h; after the reaction ended, the titanium sheet was taken out, washed with deionized water and ultrasonically treated for 10 min, filtered, and then placed in a vacuum drying oven at 80 °C for drying for 10 h to obtain vanadium dioxide nanowires.

[0069] After testing, the product was nanowires with a diameter of 30 - 100 nm and a length of 5 - 10 μm.

[0070] Application Example 2

[0071] The VO2 nanowires prepared in Example 2, acetylene black, and polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 8:1:1 as the positive electrode, a 0.2 mm commercial zinc foil as the negative electrode, and 3M Zn(CF3SO3)2 as the electrolyte to assemble a battery. After the assembled battery was left standing for 12 h, electrochemical tests were carried out on a Blue Power test system with a voltage window of 0.2 - 1.6 V.

[0072] After testing, at currents of 0.1, 0.2, 0.4, 0.6, 1, 2, 4, 6, and 10 A / g, the specific capacities were 359.8, 342.4, 336.3, 326.2, 306.7, 289.7, 269.8, 248.7 mAh / g respectively; when used as the positive electrode material of a zinc-ion battery, at a current density of 10 A / g, after 1000 cycles, the capacity reached 154.9 mAh / g and the capacity retention rate reached 68%.

[0073] Example 3

[0074] (1) Vanadium pentoxide powder was dispersed in deionized water with the molar concentration controlled at 0.5 mol / L; subsequently, tartaric acid was added as a reducing agent, and the molar ratio of the reducing agent to vanadium pentoxide was 4:1. Then it was heated to 90 °C and stirred for 2 h simultaneously to completely dissolve the vanadium pentoxide powder, forming a blue solution, denoted as Solution A.

[0075] (2) CTAB was added to Solution A and stirred to dissolve, controlling the mass fraction of CTAB to be 2%, and the pH of the solution was adjusted to 5 with ammonia water to obtain Solution B.

[0076] (3) Solution B and a titanium sheet were transferred into a hydrothermal reaction kettle, controlling the reaction temperature at 180 °C and the reaction time at 12 h; after the reaction ended, the titanium sheet was taken out, washed with deionized water and ultrasonically treated for 10 min, filtered, and placed in a vacuum drying oven at 60 °C for drying for 10 h to obtain vanadium dioxide nanowires.

[0077] After testing, the product was nanowires with a diameter of 100 - 150 nm and a length of 5 - 10 μm.

[0078] Application Example 3

[0079] The VO2 nanowires prepared in Example 3, acetylene black, and polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 8:1:1 as the positive electrode, a 0.2 mm commercial zinc foil as the negative electrode, and 3M Zn(CF3SO3)2 as the electrolyte to assemble a battery. After the assembled battery was left standing for 12 h, electrochemical tests were carried out on a Blue Power test system with a voltage window of 0.2 - 1.6 V.

[0080] After testing, at the current densities of 0.1, 0.2, 0.4, 0.6, 1, 2, 4, 6, and 10 A / g, the specific capacities are 368.5, 347.3, 339.4, 319.2, 312.7, 291.7, 270.4, and 250.8 mAh / g respectively; when used as the cathode material of a zinc-ion battery, at a current density of 10 A / g, after 1000 cycles, the capacity reaches 157.8 mAh / g, and the capacity retention rate reaches 71%.

[0081] The foregoing description of the disclosed embodiments enables those skilled in the art to practice or use the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Thus, the present invention is not intended to be limited to the embodiments shown herein but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing vanadium dioxide nanowires, characterized in that: The following steps are involved: a) mixing a vanadium source, water and a reducing agent, and performing a reduction reaction to obtain a first solution; b) mixing the first solution obtained in step a) with a surfactant and a pH regulator, adding a titanium sheet, performing a hydrothermal reaction, taking out the titanium sheet after the reaction, separating the product grown on the titanium sheet, and obtaining vanadium dioxide nanowires after drying.

2. The preparation method according to claim 1, characterized in that: The vanadium source in step a) is selected from one or more of vanadium pentoxide, ammonium metavanadate, and ammonium polyvanadate; The reducing agent is selected from one or more of oxalic acid, citric acid and tartaric acid.

3. The preparation method according to claim 1, characterized in that: In the process of mixing the vanadium source, water and the reducing agent in step a), the molar concentration of the vanadium source is controlled to be 0.1 mol / L to 0.5 mol / L; The molar ratio of the vanadium source to the reducing agent is 1:(2-4).

4. The preparation method according to claim 1, characterized in that: The temperature of the reduction reaction in step a) is 90° C. to 100° C., and the time is 1 h to 4 h.

5. The preparation method according to claim 1, characterized in that: The surfactant in step b) is hexadecyltrimethylammonium bromide, and the mass fraction after addition is 0.5% to 2.0%.

6. The preparation method according to claim 1, characterized in that: The pH regulator in step b) is ammonia water, and the pH value is adjusted to 4-6.

7. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step b) is 160° C. to 200° C., and the time is 8 h to 16 h.

8. The preparation method according to claim 1, characterized in that: The separation process in step b) is specifically as follows: After washing the titanium sheet after the reaction with water, the titanium sheet is placed in water for ultrasonication for 10 to 30 minutes, and the product grown on the titanium sheet is separated by filtration; The drying temperature is 60° C. to 80° C., and the drying time is 10 h to 15 h.

9. A vanadium dioxide nanowire, characterized in that: The preparation method is described in any one of claims 1 to 8.

10. A zinc ion battery comprising: A positive electrode, a negative electrode and an electrolyte, characterized in that the positive electrode comprises the vanadium dioxide nanowires according to claim 9.